2014
DOI: 10.3389/fmicb.2014.00153
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis for nitrate resistance in Desulfovibrio strains

Abstract: Nitrate is an inhibitor of sulfate-reducing bacteria (SRB). In petroleum production sites, amendments of nitrate and nitrite are used to prevent SRB production of sulfide that causes souring of oil wells. A better understanding of nitrate stress responses in the model SRB, Desulfovibrio vulgaris Hildenborough and Desulfovibrio alaskensis G20, will strengthen predictions of environmental outcomes of nitrate application. Nitrate inhibition of SRB has historically been considered to result from the generation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 204 publications
(83 citation statements)
references
References 62 publications
3
78
2
Order By: Relevance
“…Because SRB can occur in environments where they may be exposed to nitrite as a result of the activity of nitrate-reducing bacteria and also because nrfHA-carrying bacteria often have the ability to reduce nitrate, we tested the effect of sodium nitrate on nrfH gene expression. D. vulgaris cannot reduce nitrate, and growth is moderately inhibited by an unknown mechanism at 100 mM sodium nitrate (10,48). The WT, nrfR mutant, and JW9382 strains were exposed to 100 mM sodium nitrite at the mid-log phase for 1 h. We observed that the expression levels of the reference genes of choice, rplS and rpoD, were strongly decreased (ϳ5-to 10-fold) upon the addition of nitrate (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Because SRB can occur in environments where they may be exposed to nitrite as a result of the activity of nitrate-reducing bacteria and also because nrfHA-carrying bacteria often have the ability to reduce nitrate, we tested the effect of sodium nitrate on nrfH gene expression. D. vulgaris cannot reduce nitrate, and growth is moderately inhibited by an unknown mechanism at 100 mM sodium nitrate (10,48). The WT, nrfR mutant, and JW9382 strains were exposed to 100 mM sodium nitrite at the mid-log phase for 1 h. We observed that the expression levels of the reference genes of choice, rplS and rpoD, were strongly decreased (ϳ5-to 10-fold) upon the addition of nitrate (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Some SRB, such as Desulfovibrio alaskensis G20, lack any means for reducing the nitrite and are highly sensitive to small amounts of nitrite (10,11). However, other SRB can reduce nitrite via a cytochrome c-type nitrite reductase, NrfA, and are able to tolerate low millimolar amounts of nitrite (7,12).…”
mentioning
confidence: 99%
“…In fact, we recently reported that the Rex DvH mutant was inhibited for growth with thiosulfate as the terminal electron (33), an observation that deserves examination. In addition, Rex DvH has been predicted to regulate more than 50 genes (21).…”
Section: Discussionmentioning
confidence: 99%
“…All plasmid constructs were made by the SLIC procedure (32). The protocol used to generate the strain lacking the sat promoter (⌬P sat ), JW9293, conferring kanamycin resistance and 5-FU sensitivity, has previously been described (33). Briefly, 150 bp upstream of sat (Ϫ150 to Ϫ1) was replaced with a cassette conferring resistance to kanamycin and a counterselectable marker (upp, the gene encoding uracil phosphoribosyltransferase that confers 5-FU sensitivity to the 5-FU r parental strain).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation